2016
DOI: 10.1097/aap.0000000000000408
|View full text |Cite
|
Sign up to set email alerts
|

The Dorsal Root Ganglion as a Therapeutic Target for Chronic Pain

Abstract: Chronic neuropathic pain is a widespread problem with negative personal and societal consequences. Despite considerable clinical neuroscience research, the goal of developing effective, reliable, and durable treatments has remained elusive. The critical role played by the dorsal root ganglion (DRG) in the induction and maintenance of chronic pain has been largely overlooked in these efforts, however. It may be that, by targeting this site, robust new options for pain management will be revealed. This review su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
80
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(81 citation statements)
references
References 101 publications
0
80
0
1
Order By: Relevance
“…In amputees with phantom limb pain, Vaso et al demonstrated that dilute lidocaine applied directly to the DRG in concentrations sufficient to suppress DRG ectopic firing, but not transmission of other sensory information, was capable of abolishing phantom limb pain in topographically appropriate regions [58•]. There is also growing evidence for the effectiveness of targeted DRG stimulation in the effective alleviation of chronic neuropathic pain [59,60], and this evidence may expand as novel interfacing technologies continue to advance [61].…”
Section: Evidence For Peripheral Mechanisms: Clinicalmentioning
confidence: 98%
“…In amputees with phantom limb pain, Vaso et al demonstrated that dilute lidocaine applied directly to the DRG in concentrations sufficient to suppress DRG ectopic firing, but not transmission of other sensory information, was capable of abolishing phantom limb pain in topographically appropriate regions [58•]. There is also growing evidence for the effectiveness of targeted DRG stimulation in the effective alleviation of chronic neuropathic pain [59,60], and this evidence may expand as novel interfacing technologies continue to advance [61].…”
Section: Evidence For Peripheral Mechanisms: Clinicalmentioning
confidence: 98%
“…The DRG acts as an important modulation center for nociceptive transmission and is key in the generation and maintenance of chronic pain (30)(31)(32). The hyperexcitability in DRG neurons in NP is in part a result of changes in ion-channel functional status (4).…”
Section: Discussion Drg Under Npmentioning
confidence: 99%
“…Research supporting the efficacy and safety of DRG-S for treatment of chronic pain syndromes continues to grow. [4][5][6][7]10,12,13,16,17 Many patients with chronic pain conditions have had prior surgical interventions on the spine, and a substantial subset of patients may present with postsurgical changes in anatomy. These changes may complicate placement of DRG-S leads via the traditional anterograde approach if the surgical level was just below the target level for DRG-S.…”
Section: Discussionmentioning
confidence: 99%
“…8,9 The interlaminar approach for the insertion of percutaneous DRG-S leads has been well documented in an anterograde manner. [4][5][6][7][10][11][12] However, in patients with a history of spinal surgery at a level just below the target level for stimulation, anterograde placement of the leads can be difficult secondary to adhesions or epidural scaring. Importantly, a significant proportion of the patients with chronic pain syndromes have undergone back surgery.…”
Section: Introductionmentioning
confidence: 99%